Redox-mediated signal transduction methods and protocols - Hancock, John T.; Conway, Myra ca. 20./21. Jh (Methods in Molecular Biology, 2019)
This volume explores the scope of the cellular redox analysis and the importance of not being limited by frequently changing and evolving technology. The chapters in this book cover a wide range of topics such as redox components in animal and plant cells and the role of reactive oxygen species, reactive nitrogen species, and hydrogen sulphide in cell signaling; measuring modifications using Flow Cytometry, ELISA assays, and Western blot analysis; measurement of oxidative stress in mitochondira and biological systems; and the use of the genetically encoded fluorescent probe HyPer. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and informative, Redox-Mediated Signal Transduction: Methods and Protocols, Second Edition is a valuable resource for both novice and expert researchers who want to expand their studies into new areas and new systems in the evolving redox field.